An unusual metastatic tumor to the heart - Shima Mousavi, MD; Neda Zarrin-Khameh, MD, MPH (Elsevier, 2017)
Metastatic tumors of the heart are 20 to 40 times more common than the primary cardiac tumors. Cardiac metastasis from pelvic malignancy is rare and gynecological tumors rarely metastasize to the heart. Metastasis into the heart is rare and most of the cases are diagnosed postmortem during autopsy. We report a case of metastatic squamous cell carcinoma of uterine cervix into heart causing obstruction of the right ventricle and pulmonary artery causing dyspnea on exertion and eventually patient's demise. Keywords: Case report, Squamous cell carcinoma, Metastasis and heart